If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 + -11 = 30 + -1x Combine like terms: 29 + -11 = 18 18 = 30 + -1x Solving 18 = 30 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 18 + x = 30 + -1x + x Combine like terms: -1x + x = 0 18 + x = 30 + 0 18 + x = 30 Add '-18' to each side of the equation. 18 + -18 + x = 30 + -18 Combine like terms: 18 + -18 = 0 0 + x = 30 + -18 x = 30 + -18 Combine like terms: 30 + -18 = 12 x = 12 Simplifying x = 12
| 95-63=x-60 | | 8x-7=-10+9x | | 8x-4x-20=4 | | 89-45=90-x | | 2(2a+2)=11+3a | | 37-21=x-24 | | x-a+2=2ax-3x | | 7z-11=43+z | | a^2+11a=12 | | ln(2x+-9)=0 | | 3s^2+28x-3=0 | | F(x)=x^2-15x+15 | | 43-26=40-x | | 5.2x=31 | | 17x+12=17x-12 | | 5.2x=32 | | (1)(2)y-7=(1)(5)y | | 56-21=x-20 | | 13+74=x+70 | | 7h+10=66 | | 43+15=40+c | | (3x+1)(6x-4)= | | .4w+60=w+53 | | X+16=20+17 | | -2(2t+1)=2 | | 48+x=47+31 | | .4w+60=1w+53 | | 9-8m=17 | | (x^2)-4x=6 | | 7m+1-1=4m+6m | | -3x+6x+24=9 | | 4+x=7+2 |